Sustainable Tourism: Concept And Implementation for Sustainable Tourism Development - DEWI, Ni Komang Cantika; TRISYANI, Ni Putu Nadin; YULIANI, Ni Made Dwi; PRAMITA, Ni Kadek Diah; JAYAMAHE, Ni Putu Yulia Pasek (PT Batara Swastika Harati, 2025)
Sustainable tourism has emerged as an important paradigm in shaping the development of the modern tourism industry. This concept emphasizes the need to balance economic growth, environmental conservation, and the well-being of local communities. It not only seeks to generate economic benefits but also to preserve cultural heritage, protect natural resources, and ensure social equity for present and future generations. This study aims to analyze the concept of sustainable tourism and its implementation within the context of tourism development in Indonesia. The method employed is a literature review, which involves analyzing various national and international academic sources related to sustainable tourism practices and policies. The findings indicate that sustainable tourism requires an integrated and collaborative approach involving the government, the private sector, and local communities. Successful implementation depends on long-term planning, active participation of local stakeholders, and strong commitment from all parties. In conclusion, sustainable tourism is not merely a theoretical framework but an urgent necessity to guarantee the resilience and future sustainability of the tourism industry.